Analysis of the behavior of reinforced concrete columns strengthened with sleeve wedge bolts and a self compacting concrete layer - Marques,M. G. (2015)
Strengthening of reinforced concrete columns by jacketing is one of the most common structural rehabilitation techniques in Brazil. For adequate performance, it is necessary, among others, to avoid detachment of the new concrete layer (strengthening material) from the old concrete substrate when the strengthened member is again in service conditions. This paper describes the test results of eight reinforced concrete rectangular columns subjected to combined compression and one-axis bending to evaluate the efficiency of using sleeve wedge bolts across the new concrete/old concrete interface to avoid detachment. The strengthening technique, in this case, consists of adding a layer of self-compacting concrete to one face of the column. Two columns tested were monolithic and named PO (original column) e PR (reference column). The other six columns were strengthened using a new 35 mm thick self-compacting concrete layer attached to the column face subjected to highest compressive stresses. Column PO had a 120mm by 250 mm rectangular cross section and its results gave information about column behavior without the use of strengthening. Column PR had a 155mm by 250 mm rectangular cross section and its cross section dimensions matched the strengthened columns but it was cast monolithically. To improve bond conditions between the existing concrete and the new concrete, the concrete surface was roughened and the outermost aggregate was exposed using hydro jetting. Holes along the concrete surface were made to insert the wedge bolts responsible for increasing the bond between the two concrete surfaces. The difference among the six strengthened columns was the position and amount of bolts used. Results indicate that the position and amount of the bolts alters significantly the strength capacity of the columns, since premature rupture by concrete detachment was delayed.